PERAN DIPLOMASI PUBLIK DALAM MEMPERKUAT HUBUNGAN BILATERAL INDONESIA - AMERIKA SERIKAT PADA MASA PEMERINTAHAN SUSILO BAMBANG YUDHOYONO (2004 – 2014) - dina puspita plehanku (Universitas 17 Agustus 1945 Jakarta, 2017)
Abstract Public Diplomacy as a part of soft power has been the main principle of Indonesia’s diplomacy under President Yudhoyono. Due to the ineffectiveness of Track 1 Diplomacy, Government-to-Government (G2G) relations, in promoting the positive image of Indonesia, the role of public diplomacy becomes important. Thus, public diplomacy practice which involves all aspects of society; Government to Government (G2G), Government to People Contact (G2P), and People to People Contact (P2P), is relevant in order to promote Indonesia to American society and strengthening its bilateral relations as well. This research, therefore, is trying to discuss the role of public diplomacy in strengthening the RI-US bilateral relations and its benefits to Indonesia’s foreign policy. The findings show that public diplomacy contributes in strengthening RI-US bilateral relations by the use of public diplomacy instruments such as cultural and educational exchanges, official visits and social media. Keywords: Soft Power, Public Diplomacy, RI-US Bilateral Relations.